The Educacional Challenge of Florestan Fernandes - Carlos Bauer
The work of Florestan Fernandes, a Brazilian sociologist, (1920 - 1995), is quite broad. His intellectual output comprises more than fifty titles, including cultural issues, political, social, which include works such as the social organization of Tupinambás integration of blacks in a class society, class society and underdevelopment, dependent capitalism and social classes in America, in pursuit of socialism - last writings & other texts and the bourgeois revolution in Brazil. Contemplating also educational themes, we find, in addition to the educational challenge, Brazilian university: reform or revolution, the question of USP and Education and society in Brazil. This article is concerned with reflecting on the historical importance of the educational challenge, edited by Cortez & Associate Editors, in 1989, the construction of counter-hegemonic praxis in Brazilian education.